2004
DOI: 10.1002/cb.135
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction, loyalty and word of mouth within the customer base of a utility provider: differences between stayers, switchers and referral switchers

Abstract: Research on satisfaction, loyalty and word of mouth (WOM) behaviour has made considerable progress within recent years, but important aspects remain neglected. In this paper, it is argued that, within the customer base of service providers, certain groups can be identified which differ from each other with regards to these variables. Hypotheses are developed and tested in a sample of 765 clients of a large German energy provider. The results show that recently acquired customers (switchers) differ from long‐te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
67
2
10

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(86 citation statements)
references
References 21 publications
6
67
2
10
Order By: Relevance
“…This result is consistent with previous results research (Anderson, 1998;Bolton & Drew, 1992;Herr et al, 1991;Wangenheim & Bayon, 2004;Wangenheim & Bayon, 2007). For example, Anderson (1998) showed that customers with a higher level of satisfaction engage to a greater extent in positive informal interpersonal verbal communication, recommending products from the company where they are customers.…”
Section: Research Conclusion and Limitationssupporting
confidence: 91%
See 1 more Smart Citation
“…This result is consistent with previous results research (Anderson, 1998;Bolton & Drew, 1992;Herr et al, 1991;Wangenheim & Bayon, 2004;Wangenheim & Bayon, 2007). For example, Anderson (1998) showed that customers with a higher level of satisfaction engage to a greater extent in positive informal interpersonal verbal communication, recommending products from the company where they are customers.…”
Section: Research Conclusion and Limitationssupporting
confidence: 91%
“…Literature offers enough arguments to support the relationship between satisfaction and positive interpersonal verbal communication (Athanassopoulos et al, 2001;Bitner, 1990;Hartline & Jones;Swan & Oliver, 1989), while satisfaction, respectively dissatisfaction to a consumption experience are the main antecedents of WOM communication (Anderson, 1998;Bolton & Drew, 1992;Herr et al, 1991;Schlesinger & Heskett, 1991;Wangenheim & Bayon, 2004;Wangenheim & Bayon, 2007 …”
Section: H5: There Is a Positive Direct Relationship Between Satisfacmentioning
confidence: 99%
“…However, some researchers have focused on customers creating WOM behavior (Bitner 1990Gruen et al 2006Hennig-Thurau et al 2004Reichheld and Earl Sasser 1990Yoo et al 2013). For example, Wangenheim (2004) investigated the difference in creating WOM behavior among stayers and switchers. The role of opinion leadership in generating WOM is also dealt with (Richins and Root-Shaffer 1988).…”
Section: Word Of Mouthmentioning
confidence: 99%
“…Loyalty is an attitude; it refers to positive feelings towards a brand in addition to repurchasing time after time. 25 It includes both attitudinal and behavioural practices, such as repeat buying of a product and service, repurchasing a brand for a long period of time, non-sensitivity to price increases, 26,27 a relational construct where repeat behaviour and psychological bond are closely connected, 28 a higher possibility of introducing or recommending companies to others and establishing positive public word-of-mouth . 29 With reference to the above defi nition, customer loyalty has been generally described as occurring when customers repeatedly purchase goods or services over time and hold favourable attitudes towards, and support, the company supplying the goods or services.…”
Section: Customer Loyaltymentioning
confidence: 99%